Comparison of Energy Feeding Programs and Early Feed Restriction on Live Performance and Carcass Quality of Large Male Broilers Grown for Further Processing at 9 to 12 Weeks of Age - Saleh, E.A.; Watkins, S.E.; Waldroup, A.L.; Waldroup, P.W. (International Journal of Poultry Science, 2003)
Six feeding programs for broilers based on level and time of feeding poultry oil (PO) were compared as well as early feed restriction. All diets were formulated to contain a minimum of 107.5% of NRC (1994) amino acid recommendations, maintained in proportion to dietary energy level. Three different energy levels within each age period were obtained by adding 0, 3, and 6% PO and formulating for optimum nutrient density. Diets within each age period (starter, 0 to 21 days; grower, 21 to 42 days; and finisher, 42 to 84 days) had similar calorie:protein ratios. During the restriction period of 7 to 14 d, the birds were given an amount of their respective diets calculated to provide daily maintenance energy requirements. Before and after the restriction period, the birds were offered feed for ad libitum consumption. Body weight, feed consumption, and processing quality were obtained at 63, 70, 77, and 84 d of age. In general, body weight and feed conversion were improved as PO was added to the diet; however, the response was not always significant. Mortality, dressing percentage, abdominal fat, breast, leg, and wing yield did not differ significantly as various levels of PO were fed. In the few instances where there was a significant difference, it did not follow any specific trend among the dietary treatments. There was a significant decrease in the ability to utilize energy by birds grown to 63, 70, 77, or 84 d as the level of PO increased. Feed restriction reduced body weight at 63, 70, and 77 d of age. However, feed conversion was significantly improved and mortality significantly reduced at all ages as compared to birds fed ad libitum. Feed restriction had little impact on abdominal fat. No interaction was observed between PO levels and feed restriction.